2018
DOI: 10.1038/s41598-018-28877-x
|View full text |Cite
|
Sign up to set email alerts
|

Probing disorder in pyrochlore oxides using in situ synchrotron diffraction from levitated solids–A thermodynamic perspective

Abstract: Pyrochlore, an ordered derivative of the defect fluorite structure, shows complex disordering behavior as a function of composition, temperature, pressure, and radiation damage. We propose a thermodynamic model to calculate the disordering enthalpies for several RE2Zr2O7 (RE = Sm, Eu, Gd) pyrochlores from experimental site distribution data obtained by in situ high temperature synchrotron X-ray diffraction. Site occupancies show a gradual increase in disorder on both cation and anion sublattices with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…High temperature in situ diffraction and differential scanning calorimetry studies can be done in the future to nd the temperature dependence of the equilibrium degree of disorder and provide a more realistic thermodynamic model, as has been done for other pyrochlore compounds. 93 However, since at present we have data only for one series of quenched materials, we cannot say anything denitive about the equilibrium degree of ordering and resulting congurational entropy. Further local structure and calorimetry studies of more uorite-related systems would provide insights about the relation between local structure and thermodynamics.…”
Section: Thermodynamic Datamentioning
confidence: 98%
“…High temperature in situ diffraction and differential scanning calorimetry studies can be done in the future to nd the temperature dependence of the equilibrium degree of disorder and provide a more realistic thermodynamic model, as has been done for other pyrochlore compounds. 93 However, since at present we have data only for one series of quenched materials, we cannot say anything denitive about the equilibrium degree of ordering and resulting congurational entropy. Further local structure and calorimetry studies of more uorite-related systems would provide insights about the relation between local structure and thermodynamics.…”
Section: Thermodynamic Datamentioning
confidence: 98%
“…The adequate and accurate computational methodology (see Section 2) substantially improved the DFT prediction of the temperature of order-disorder transitions and allowed for derivation of accurate maps of cation antisite and anion Frenkel pair defect formation energies [27,103] (Figure 9), which were recently shown to be the best match to the experimental values. [104] As shown in Figure 9, the obtained maps reveal a clear correlation between the oxygen Frenkel pair defect formation energies and the stability field of pyrochlore. Li et al [27] showed that the compounds that form defect fluorite have small or negative Frenkel pair defect formation energy.…”
Section: Retention Of Radium Within the Repository Systemmentioning
confidence: 65%
“…However, a pure simulation driven research that aims at understanding the performance of pyrochlore as a nuclear waste form on the atomic scale has also been applied. The adequate and accurate computational methodology (see Section ) substantially improved the DFT prediction of the temperature of order–disorder transitions and allowed for derivation of accurate maps of cation antisite and anion Frenkel pair defect formation energies (Figure ), which were recently shown to be the best match to the experimental values . As shown in Figure , the obtained maps reveal a clear correlation between the oxygen Frenkel pair defect formation energies and the stability field of pyrochlore.…”
Section: Materials Research For Nuclear Waste Management In Jülichmentioning
confidence: 91%
“…In situ synchrotron diffraction coupled with aerodynamic levitation was performed on Eu 2 Zr 2 O 7 to study the structural progression of disorder upon increasing temperature ( Maram et al, 2015 ). This was followed by in situ synchrotron diffraction on various zirconium and hafnium-based pyrochlores, RE 2 Zr 2 O 7 (RE = Sm, Eu, and Gd) and RE 2 Hf 2 O 7 (RE = La, Nd, and Sm), and modeling of the thermodynamics of disordering using configurational entropy calculations based on cation and anion site occupancies obtained from Rietveld refinement ( Maram et al, 2018 ). This study extended early work on spinel disordering to fluorite-related systems ( Navrotsky and Kleppa, 1967 ).…”
Section: Fluorite-derived Structuresmentioning
confidence: 99%